2008
DOI: 10.1677/jme-08-0066
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation of glucocorticoid-induced leucine zipper in the developing anterior pituitary gland

Abstract: The expression profile of glucocorticoid-induced leucine zipper (GILZ) in the anterior pituitary during the second half of embryonic development in the chick is consistent with in vivo regulation by circulating corticosteroids. However, nothing else has been reported about the presence of GILZ in the neuroendocrine system. We sought to characterize expression and regulation of GILZ in the chicken embryonic pituitary gland and determine the effect of GILZ overexpression on anterior pituitary hormone levels. Pit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…We have previously reported that GILZ modulates the immune response after SCI suggesting a potential role due to therapeutic effects . Moreover, GILZ appears to be a marker of response to GC and is basally expressed in central nervous system .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…We have previously reported that GILZ modulates the immune response after SCI suggesting a potential role due to therapeutic effects . Moreover, GILZ appears to be a marker of response to GC and is basally expressed in central nervous system .…”
Section: Resultsmentioning
confidence: 96%
“…It mediates a number of GC effects such as control of cell proliferation, apoptosis, and differentiation, including in T cells . Notably, GILZ is expressed in different areas of the CNS, such as forebrain, spinal cord, and cerebellum .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, GILZ is up-regulated by GCs and IL-10 in human mast cells (59); by GCs and IL-15 in natural killer (NK) and NKT cells (60); by GCs, erythropoietin (Epo), and stem cell factor (SCF) in primary erythroid progenitors (61); and by GCs, IL-10, and transforming growth factor ␤ (TGF-␤) in human immature DCs (35). Furthermore, GILZ is up-regulated by GCs in embryonic pituitary gland in the chick and regulates the expression of several pituitary hormones (62).…”
Section: Structure and Basic Regulation Of Gilz Expressionmentioning
confidence: 99%
“…It is rapidly induced by glucocorticoids in T lymphocytes [ 6 - 8 ], macrophages, dendritic cells and mast cells [ 9 - 11 ]. GILZ expression in the anterior pituitary during embryonic development in the chick is consistent with regulation by corticosteroids [ 12 ]; in the kidney cortical collecting duct, GILZ is induced by aldosterone [ 13 ]; and in human cervical adenocarcinoma HeLa cells, GILZ expression is controlled by estradiol [ 14 ].…”
Section: Introductionmentioning
confidence: 98%